Physical and biochemical characterization of dromedary milk as traditionally consumed by Bedouins - Hasni, Sara; Khelil, Aminata; Mahcene, Zineb; Bireche, Kamilia; Cebi, Nur; Rahmani, Youcef; Brahimi, Zakaria; Ahhmed, Abdulatef (ELSEVIER SCI LTD, 2023)
Few studies were dedicated to characterizing the dromedary milk (DM) as consumed by Bedouins, mixed with a small amount of dromedary urine (DU). Therefore, this work aimed to reveal some physical and biochemical characteristics of the DM alone, and incorporated with DU at two different concentrations. pH, colour, Brix, fats, and minerals were evaluated with proteins and sugar content using FTIR; in addition to protein oxidation. The results showed that DM counts as a rich source of the nutritional element yet its proprieties were affected by the addition of DU. An important increase in colour, sugar, fat, and protein concentration with a remarkable augmentation in the pH, mineral content, and protein oxidation where the more urine is added the more milk proteins are oxidated as demonstrated by the characteristics showed in the two mixtures which will negatively affect DM therapeutical proprieties, especially the one related to proteins.
Keywords: Dromedary milk; Mixture; Physical proprieties; Biochemical characterization; Protein oxidation; CAMEL MILK; QUANTIFICATION; ANTICANCER; URINE; Chemistry; Food Science & Technology; Nutrition & Dietetics